Operational performance of tractor running with diesel and biodiesel from buriti oil (Mauritia flexuosa) - Iamaguti, Priscila Sawasaki [UNESP]; Lopes, Afonso [UNESP]; De Oliveira, Melina Cais Jejcic [UNESP]; Neves, Murilo Coelho Theodoro [UNESP]; Lira, Thyago Augusto Medeiro [UNESP]; Moreti, Thaisa Calvo Fugineri [UNESP]; De Lima, Leomar Paulo; Koike, Gilberto Hirotsugu Azevedo (Southern Cross Publishing, 2016)
Biodiesel is made from vegetable oils, animal fats or residual oil by reaction with ethanol or methanol, renewable fuel sources decrease environmental problems. The purpose of this study is to evaluate the operational performance and smoke density of an agricultural tractor running ethyl biodiesel from buriti oil (Mauritia flexuosa), diesel B S50 and diesel B S1800. Each type of diesel was mixed with biodiesel according proportions B0, B5, B15, B25, B50 and B75, in which the number indicates the percentage of biodiesel in diesel. Fuel consumption (volumetric, weight, and specific), drawbar force and power, real travel speed and smoke density were evaluated. Replacing B S1800 and B S50 (B0 diesels) with B100 reduced smoke density by 33.33% and 28.90%, respectively. The results showed an increase of 5.41% in specific fuel consumption comparing B0 and B100. Finally, biodiesel can be considered totally or as blending for fueling tractors.
Keywords: Density of smoke; Fuel; Specific consumption; Tillage; Tractor test